2018
DOI: 10.1037/ppm0000109
|View full text |Cite
|
Sign up to set email alerts
|

The protagonist, my Facebook friend: How cross-media extensions are changing the concept of parasocial interaction.

Abstract: More and more TV series are using cross-media extensions like smartphone applications and social networking sites to connect with the audience. Because these features facilitate the recipient's interaction with a media persona, they can be assumed to influence the perceived parasocial interaction (PSI; Horton & Wohl, 1956). The goal of the present paper was to investigate the connection between cross-media extensions of a social TV series and the PSI with its protagonist. To this aim, a social TV series was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…al 2014 ) as has PSRs with news anchors on Facebook (Farmer 2012 ). Cross-media extensions such as friending a fictional TV character who has a Facebook account has been shown to increase parasocialization with characters (Kyewski et al 2018 ). Likely because social networking sites are used for marketing as well as entertainment, much consumer research has also examined PSI on social networking platforms.…”
Section: Brief Summary Of Relevant Parasocial Researchmentioning
confidence: 99%
“…al 2014 ) as has PSRs with news anchors on Facebook (Farmer 2012 ). Cross-media extensions such as friending a fictional TV character who has a Facebook account has been shown to increase parasocialization with characters (Kyewski et al 2018 ). Likely because social networking sites are used for marketing as well as entertainment, much consumer research has also examined PSI on social networking platforms.…”
Section: Brief Summary Of Relevant Parasocial Researchmentioning
confidence: 99%
“…Based on previous research indicating that actual interaction on social media promotes the experience of PSI (e.g., Kyewski et al, 2018), in the present study, we assumed that followers' actual interaction on social media, in terms of watching posts, commenting, or liking, would support the experience of PSI with the historical figure Sophie Scholl. Hence, we derived the following hypothesis:…”
Section: Psi With Historical Figures On Social Mediamentioning
confidence: 88%
“…Therefore, there is an intensive discussion in the literature of whether the concept of PSI can be transferred to social media (e.g., Gleich, 2022). Studies transferring PSI to the research field of social media have indeed shown that this novel manner of reciprocal interaction positively affects the experience of PSI (Kowert & Daniel, 2021;Kyewski et al, 2018). For example, Kyewski and colleagues (2018) demonstrated that actual interaction (e.g., commenting) impacts PSI with a fictional character on Facebook.…”
Section: Posting From Thementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Lou (2021) defines this relation as a more enhanced version of parasocial relation -or the so-called trans-parasocial relation -and describes it as collectively reciprocal, (a)synchronously interactive and co-created. Indeed, the interactive nature of social media platforms allows influencers to address their followers directly through their posts, thus overcoming the fourth wall and intensifying PSRs (Kyewski et al, 2018). According to Berryman and Kavka (2017), such posts are an "expressive performance of vulnerability" (p. 313) that appears to invite the audience into the influencer's personal life.…”
Section: Social Media Influencersmentioning
confidence: 99%